BIOPHILIC DESIGN AS A MEANS OF HARMONIZNG THE ARCHITECTURAL ENVIRONMENT - Токар, Віктор; Горгола, Дар'я; Нестеренко, Діана (SWorldJournal, 2025)
The article explores biophilic design as an innovative concept for harmonizing urban environments through the integration of natural elements into architecture. The main principles, forms, and methods of biophilic design are examined, along with its impa